THEORETICAL APPROACHES IN THE COMPARATIVE ANALYSIS OF MODERN PROSE (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
The problem of image creation in literature and the research of knowledge and skills obtained by comparing images is one of the urgent issues of today's modern literature. By comparing the images in each work, in the process of comparative analysis, new information is obtained about the compared object. This thesis examines important theoretical approaches in the comparative analysis of modern prose.